Influential factors and model of shale pore evolution: A case study of a continental shale from the Ordos Basin. (April 2019) - Wang, Feiteng; Guo, Shaobin
Abstract: Pore characteristics have a significant influence on the occurrence and enrichment of shale gas. Therefore, these characteristics are key parameters in shale reservoir evaluation and have important research significance. Taking a continental shale sample from the Ordos Basin, China as an example, this research used low-pressure CO2 /N2 adsorption, high-pressure mercury intrusion porosimetry (MIP), vitrinite reflectance (Ro) analysis, hydrocarbon generation measurements, X-ray diffraction analysis and argon ion polishing-field emission scanning electron microscopy (AIP-FESEM) in conjunction with a thermal simulation experiment to study pore characteristics. Through the above analyses, this study achieved a whole-aperture dynamic characterization of the shale pores and discussed the characteristics of the shale pore distribution and evolution through geological history. Then, the factors influencing pore evolution were analysed and a pore evolution model was established. The results showed that the micropores and mesopores provided the majority of the surface area in the sample, while the mesopores and macropores provided the majority of the pore volume in the sample. During the thermal simulation experiment, pore evolution was dominated by the hydrocarbon generation by organic matter, the transformation of minerals and compaction. According to the pore evolution characteristics and the main influential factors during the thermal simulation experiment, the pore evolution model can be divided into four stages. The characteristics of the micropores, mesopores, macropores and the influential factors differ in each stage. Highlights: Pore distribution and evolution characteristics through geological history were revealed by whole-aperture dynamic characterization. The pore evolution model was established and divided into four stages.